Quality methods in virtual and augmented reality with a focus on education: a systematic literature review - Amelie Karcher; Dominik Arnold; Bernd Kuhlenkötter (Management Review Quarterly, 2024)
With the goal of developing a unified approach for implementation of training for quality methods—with the help of innovative assistance systems—the current state of research is determined within the scope of this work. These quality methods include Quality Management Systems such as Lean Management and Six Sigma. A systematic literature search is conducted to determine the current state of research on Augmented and Virtual Reality data glasses, which are considered here as innovative assistance systems. This search extends without restriction to the date of data collection at the beginning of the year 2022, as Augmented and Virtual Reality data glasses are considered to be particularly immersive technologies. Based on the databases Scopus and Web of Science, an extended systematic literature review was used for the research. By answering the research question and classifying the implemented research work, an overview of the current state of virtual and augmented reality research will be given. This makes it clear that further research is needed, especially with regard to the training of quality methods, to develop specific models and action guidelines.
Keywords: I25; 650; Augmented reality; Virtual reality; Systematic literature review; Lean management; Six Sigma; Quality methods